Immediate Echocardiographic Surveillance After Transcatheter Closure of a Patent Ductus Arteriosus: A Feasible Method to Assess Residual Shunt - Chi-Di Liang; Sheung-Fat Ko; Chien-Fu Huang; Shao-Ju Chien; Ying-Jui Lin; I-Chun Lin; Mao-Meng Tiao (Elsevier, 2010)
To evaluate the feasibility of echocardiography after transcatheter closure of patent ductus arteriosus (PDA) with coils. Methods: Between April 1998 and December 2006, 131 patients had transcatheter coil occlusion of their PDA using Gianturco coils. We hypothesized that post-procedural hemolysis would not occur if a residual shunt < 1 mm or if no continuous waveform was detected by echocardiography. Immediately after coil implantation, patients without and with a residual shunt as detected by echocardiography were designated to groups A and B, respectively. The clinical presentations, laboratory data and outcomes were compared between the two groups. Results: There were 101 patients in group A and 30 patients in group B. Patients in group B had larger ductal diameter (2.8 ± 0.9 mm vs. 1.6 ± 0.8 mm; p < 0.001), larger Qp/Qs (1.9 ± 0.9 vs. 1.3 ± 0.4; p = 0.001), higher frequency of more than one coil used (14/30 vs. 11/101; p < 0.001), and female predominance (22/30 vs. 53/101; p = 0.043) compared with group A. Trivial residual shunt was noted in 6 patients in group A and 20 patients in group B on the day after embolization. All shunts spontaneously closed within 6 months in patients of group A, while five patients in group B had a persistent shunt at the 1-year follow-up and thereafter. Although the patients in group B had higher residual shunt rate than group A during follow-up (p < 0.001), none of these patients suffered from hemolysis. Conclusion: Echocardiography is a feasible tool to assess residual shunt after PDA closure. If a residual shunt < 1 mm or if no continuous waveform is detected by echocardiography, the risk of developing hemolysis is low.